Evaluation of microplastics in sewage sludge from industrial wastewater treatment activities - Manh, Do Van; Long, Huynh Duc; Thao, Le Xuan Thanh; Ngo, Vu Dinh; Truc, Phan Nhu; Thom, Dang Thi (Vietnam Journal of Science and Technology, 2022)
The preliminary screening of microplastics (MPs) in sewage sludge from centralized industrial wastewater treatment plants (WWTPs) in Da Nang city of Viet Nam was investigated in this study. The MPs samples were collected in the sewage sludge from two WWTPs namely Hoa Cam (HC) and Hoa Khanh (HK). The obtained results indicated that the concentrations of MPs in the sewage sludge of HC and HK were 1,164 and 3,745 particles/kg dry weight, respectively. The MPs sizes varied from 1.6 to 5,000 μm, of which the size in the range of 1.6 - 100 μm was dominant at HC (42.5 %) and HK (51.8 %). The shape of MPs was mainly in the form of fragments and fibers. The MPs colour was also observed and the results showed that black, grey and yellow were the main colours of MPs. In addition, MPs chemical composition was determined and the results indicated that polyethylene terephthalate (PET) and polyethylene (PE) were dominant with 36.7 % and 25.2 % for HK and 23.5 % and 25.8 % for HC, respectively.